Past, Present and Future Ultrasonographic Techniques for Analyzing Ovarian Masses. (May 2015) - Guerriero, Stefano; Saba, Luca; Alcazar, Juan Luis; Pascual, Maria Angela; Ajossa, Silvia; Perniciano, Maura; Piras, Alba; Sedda, Federica; Peddes, Cristina; Fabbri, Paola; Pilla, Federica; Zajicek, Michal; et al.
Ultrasonography is today the method of choice for distinguishing between benign and malignant adnexal pathologies. Using pattern recognition several types of tumors can be recognized according to their characteristic appearance on gray-scale imaging. Color Doppler imaging should be used only to perform a semiquantitative color score or evaluate the flow location. International Ovarian Tumor Analysis group had standardized definitions characterizing adnexal masses and suggested the use of 'simple rules' in premenopausal women. Recently, the use of 3D vascular indices has been proposed but its potential use in clinical practice is debated. Also computerized aided diagnosis algorithms showed encouraging results to be confirmed in the future.